Perancangan Interior Pusat Informasi Ikan Predator - John Kevin (Intra, 2017)
This design background are the problem of the lack of public knowledge about potential predatory fish, especially freshwater fish that can be ornamental fish. This Predator Fish Information Center accommodates the community to obtain various information about predator fish, especially freshwater predator fish. The concept of the design is Artlantis which is a combination of the word art and atlantis which is the legend of the city under the sea, with the people expected to fell the atmosphere of buildings in ancient greek era savor the beauty of predatory fish in a large aquarium. Upon entering the entrance door visitors are invited to follow the path to enter and there is a 5m diameter aquarium center which is a combination of all fish. In addition visitors are pampered. The use of materials in the form of natural stones will bring visitors to feel in the ancient greek era with large buildings. Ceiling made curved and use the blue color makes visitors feel at the bottom of the sea plus the use of concrete material on the floor that makes visitors like being on the sand of the sea. Lastly before visitors come home, can buy souvenirs at souvenir shop or take pictures on photo booth area as a memento.